THE INFLUENCE OF POLICY IMPLEMENTATION ON THE EFFECTIVENESS OF ACCELERATION OF ELECTRONIC ID CARD RECORDING - Reyta, Fitriani (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
The problem in this research is the ineffective yet the acceleration of electronic ID card recording. Based on the phenomenon, the researcher suspects that the problem is influenced by policy implementation variables. Based on these problems, the proposed problem is: "How Big is the Effect of Implementation of Local Government Policy on the Effectiveness of Accelerating the Recording of electronic ID card".The analysis of the research problem is done by using the theory of policy implementation of George C. Edwards III in Subarsono (2005: 90), based on the factors of policy implementation through the dimension of Communication, Resources, Executor Attitude and Structure of Bureaucracy. As for the effectiveness, variables used approach theory Mahmudi (2005: 92) adapted from Steers (1985: 53) consists of the achievement of goals, integration, and adaptation. Based on the theoretical approach, the proposed hypothesis is: "The magnitude of the influence of the implementation of local government policy on the effectiveness of accelerating the recording of electronic ID card in District X is determined by the implementation of communication factors, resources, executor attitude and bureaucracy structure".Methods in this research are explanatory survey method (explanatory survey method) while the source of data collection by using literature study and field study covering: questionnaire, observation, and interview. Sampling technique used is Simple Random Sampling. The data analysis technique used is linear regression analysis.Based on the results of data processing conducted obtained the results of research that shows a positive and significant relationship between the implementation of the policy on the Effectiveness of Acceleration of Electronic ID Card Recording in District X in Bandung. Thus the hypothesis proposed in this study was tested empirically. Keywords:      policy implementation, the effectiveness of electronic recording. The issue in this research is how ineffective the acceleration of electronic ID card recording is. Based on said phenomenon, the researcher suspects that the problem is influenced by policy implementation variable. Based on this issue, the proposed research question is: "How Significant the Effect of Implementation of Local Government Policy on the Effectiveness of Accelerating the Recording of Electronic ID Card is". The analysis of the research question was done using the theory of policy implementation by George C. Edwards III in Subarsono (2005: 90), based on the factors of policy implementation through the dimension of communication, resources, executor atti- tude and structure of bureaucracy. As for the effectiveness variable, the theoretical approach by Mahmudi (2005: 92) adapted from Steers (1985: 53) was used, consisting of the achievement of goals, integration, and adaptation. Based on the theoretical approach, the proposed hypothesis is: "The significance of the influence of the implemen- tation of local government policy on the effectiveness of accelerating the recording of electronic ID card in District X is determined by the implementation of communication, resources, executor attitude and bureaucracy structure factors". Methods used in this research are explanatory survey method, while data were collected through litera- ture study and field study covering: questionnaire, observation, and interview. Sampling technique used is Simple Random Sampling. The data analysis technique used is linear regression analysis. Based on the result of data processing conducted, research result obtained shows a positive and significant relationship between the imple- mentation of the policy and the Effectiveness of Acceleration of Electronic ID Card Recording in District X in Bandung. Thus the hypothesis proposed in this study has been proven empirically.Keywords : Policy Implementation, The Effectiveness of Electronic Recording.